Penanaman Nilai Religius melalui Praktik Budaya dalam Novel Hati Suhita karya Khilma Anis - Siti Rohayah; Hespi Septiana (Jurnal Bahasa dan Sastra, 2023)
The purpose of this study is to discuss the implantation of religious values using cultural practices as a form of human relationship with God, as a form of human relationship with fellow human beings, and as a form of human relationship with oneself in the novel Hati Suhita. This study uses a literary sociology approach with a descriptive qualitative research type. The data source used is the novel Hati Suhita (2019) by Khilma Anis. Data collection techniques using reading and note techniques. The data analysis technique used is descriptive analysis technique which consists of classifying, analyzing and drawing data conclusions. The method used to test the validity of the data is the triangulation technique. The study suggests that the novel employs cultural practices to nurture religious principles, incorporating aspects such as faith, prayer, and human-God connections, as well as fostering religious attributes through human-human interactions like fairness, preaching, and companionship, while also promoting individual religious values through qualities like patience, obedience, and integrity.